Vitamin D supplementation improves the metabolic syndrome risk profile in postmenopausal women - Ferreira, P. P. [UNESP] (2019)
Objective: This study aimed to evaluate the effect of isolated vitamin D (VD) supplementation on the metabolic syndrome (MetS) risk profile in postmenopausal women. Methods: In this double-blind, placebo-controlled trial, 160 postmenopausal women aged 50-65 years were randomized into two groups: VD group, supplementation with 1000 IU vitamin D-3/day (n = 80); or placebo group (n = 80). The intervention time was 9 months, and the women were assessed at baseline and endpoint. Clinical and anthropometric data were collected. Biochemical parameters, including total cholesterol, high-density lipoprotein, low-density lipoprotein, triglycerides, glucose, and insulin, were measured. The plasma concentration of 25-hydroxyvitamin D (25(OH)D) was measured by high-performance liquid chromatography. Results: After 9 months, there was a significant increase in the 25(OH)D levels for VD group (+45.4%, p < 0.001), and a decrease (-18.5%, p = 0.049) in the placebo group. In the VD group, a significant reduction was observed in triglycerides (-12.2%, p = 0.001), insulin (-13.7%, p = 0.008), and the homeostasis model assessment of insulin resistance (-17.9%, p = 0.007). In the placebo group, there was an increase in glucose (+6.2%, p = 0.009). Analysis of the risk adjusted for age, time since menopause, and body mass index showed that women supplemented with VD had a lower risk of MetS (odds ratio [OR] 0.42; 95% confidence interval [CI] 0.21-0.83), hypertriglyceridemia (OR 0.43; 95% CI 0.22-0.85), and hyperglycemia (OR 0.23; 95% CI 0.10-0.52) compared to the placebo group (p < 0.05). Conclusions: In postmenopausal women with VD deficiency, isolated supplementation with 1000 IU vitamin D-3 for 9 months was associated with a reduction in the MetS risk profile. Women undergoing VD supplementation had a lower risk of MetS, hypertriglyceridemia, and hyperglycemia.